Ouside Cover Picture: Plasma Process. Polym. 11/2019. Issue 11 (3rd November 2019) - Liu, Zhijie; Xu, Han; Zhou, Chunxi; Wang, Wei; Liu, Dingxin; Kong, Michael G.
Abstract : Outside Front Cover : Plasma‐surface interaction plays a prominent and fundamental role in practical applications. In our work, the behaviors of modes interconversion for interfacial pattern regarding glow‐like He APPJ interacting with ITO substrate are investigated. The results reveal that interfacial pattern displays diffuse and streamer modes, which are not independent and would interconvert each other. This work is significant for deeply insights into physicochemical nature during plasma‐surface interaction. Further details can be found in the article by Zhijie Liu, Han Xu, Chunxi Zhou, Wei Wang, Dingxin Liu, and Michael G. Kong (1900108 ).